Determining the isotropic cloud point of carbon nanotube/chlorosulfonic acid solution using UV–vis–nIR absorbance saturation behavior. (March 2021) - Lee, Haemin; Lee, Dong-Myeong; Lee, Cheol-Hun; Lee, Jaegeun; Lee, Kun-Hong
Abstract: We propose a reliable and accurate method that uses ultraviolet–visible–near infrared absorbance to measure the isotropic-cloud point (ICP) of carbon nanotube (CNT)/chlorosulfonic acid (CSA) solutions. This information is necessary to improve understanding of the isotropic-to-nematic transition of CNT/CSA solutions and to guide solution processing and characterization of CNTs. In this method, the ICP of CNT/CSA solutions is defined as the CNT concentration at which the absorbance at 600 nm is saturated. This wavelength was selected as suitable by considering the resonance ratio and mass absorption coefficient. The reliability of the method was tested by comparing the ICPs measured using this method to those measured by a method that uses polarized optical microscopy and by a method that uses centrifugation. The results obtained using the three methods were consistent. An inverse proportionality between the ICP of CNT/CSA solutions and the CNT aspect ratio (AR) was confirmed; this result further confirms the reliability of our method. The AR of unknown CNTs can be predicted from the ICP of a CNT/CSA solution. Hence, this method provides a new tool to estimate the AR of unknown CNTs. Graphical abstract: Image 1